Glucocorticoids and antivirals for HBV reactivation in onco-hematologic patients - Michela di Fonzo; Andrea Marengo; Alfredo Marzano; Antonella Ferrari; Bruno Monarca; Gianfranco delle Fave; Massimo Marignani (Mediterranean Journal of Hematology and Infectious Diseases)
<!--[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-hyphenate:none; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:AR-SA;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 2.0cm 2.0cm 2.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->Patients with inactive or occult hepatitis B virus infection and onco-hematological malignancies are at risk for hepatitis flare, hepatic failure and death due to chemotherapy-mediated reactivation. Nucleot(s)ide analogues can reduce reactivation risks and/or hepatitis. However, immuno-mediated phenomena concur to determine liver damage and clinical outcome. We describe two patients with onco-hematological and hepatitis B reactivation after chemotherapy in whom glucocorticoids were added to nucleot(s)ide. Antiviral therapy was effective on replication, while glucocorticoids managed hyperergic response. One patient without underlying liver disease survived, while the second died. In this later autopsy detected cirrhosis, not evident at presentation. This clinical experience suggests that in patients with onco-hematological and persistent liver function tests alterations in spite of effective antiviral response, glucocorticoids could control the effects of immune response. However prognosis and survival are related to the underlying liver status